(untitled) (Editora Impacto Científico, 2025)
Childhood and adolescence are fundamental stages of human development, characterized by intense physical, cognitive, emotional, and social transformations. During this period, experiences and interactions shape identity and influence the trajectory toward adult life. However, in contemporary society, the phenomenon of adultization has advanced, marked by the premature exposure of children and adolescents to responsibilities, aesthetic standards, and expectations typical of the adult world. This process undermines the right to childhood and generates significant impacts on mental health and overall development, in clear contrast with the principle of Integral Protection guaranteed by current legislation. In light of this issue, the present study seeks to analyze adultization through the lens of Integral Protection, enshrined in the 1988 Federal Constitution and the Statute of the Child and Adolescent (Law No. 8,069/1990). To this end, it aims to understand the concept of childhood in different historical and cultural contexts, identify the causes and manifestations of adultization, examine legal mechanisms to confront the phenomenon—such as the Digital Statute of the Child and Adolescent (Law No. 15,211/2025) and the right to image and privacy—and assess the effectiveness of Integral Protection in addressing contemporary challenges, particularly within the digital environment. This research, based on bibliographic methodology, draws on books, scientific articles, and legal documents to construct a theoretical framework and provide critical analysis of the topic. The objective is to demonstrate that adultization is not merely a cultural phenomenon but a violation of fundamental rights, requiring legal and social responses to ensure that children and adolescents fully experience their condition as individuals in development. DOI: https://doi.org/10.56238/edimpacto2025.090-069